2005
DOI: 10.1523/jneurosci.3014-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Selective Requirement of Pax6, But Not Emx2, in the Specification and Development of Several Nuclei of the Amygdaloid Complex

Abstract: The amygdaloid complex is a group of nuclei that are thought to originate from multiple sites of the dorsal and ventral telencephalic neuroepithelium. The mechanisms that regulate their development are essentially unknown. We studied the role of Pax6 and Emx2, two transcription factors that regulate regional specification and growth of the telencephalon, in the morphogenesis of the amygdaloid complex. We used a set of specific marker genes that identify distinct amygdaloid nuclei to analyze Pax6/Small eye and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
180
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(213 citation statements)
references
References 38 publications
(73 reference statements)
33
180
0
Order By: Relevance
“…Although it has been suggested that the LCS provides cells to the ventrolateral neocortex, piriform cortex, endopiriform nucleus, claustrum (Bayer and Altman, 1991), and the dense cell layer of the olfactory tubercle (Tamamaki et al, 2001), little is known regarding the developmental profile of this migratory stream and the genetic factors governing its development. Here, consistent with previous studies (Stoykova et al, 1996;Puelles et al, 2000;Hirata et al, 2002;Tole et al, 2005), we show that the LCS is a heterogeneous population comprised of separate pallial Pax6 ϩ -derived and subpallial Dlx2 ϩ -derived cells. Our data also interestingly indicate that the LCS is comprised of an additional population of progenitor cells that coexpress both pallial (Pax6) and subpallial (Dlx2) markers.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although it has been suggested that the LCS provides cells to the ventrolateral neocortex, piriform cortex, endopiriform nucleus, claustrum (Bayer and Altman, 1991), and the dense cell layer of the olfactory tubercle (Tamamaki et al, 2001), little is known regarding the developmental profile of this migratory stream and the genetic factors governing its development. Here, consistent with previous studies (Stoykova et al, 1996;Puelles et al, 2000;Hirata et al, 2002;Tole et al, 2005), we show that the LCS is a heterogeneous population comprised of separate pallial Pax6 ϩ -derived and subpallial Dlx2 ϩ -derived cells. Our data also interestingly indicate that the LCS is comprised of an additional population of progenitor cells that coexpress both pallial (Pax6) and subpallial (Dlx2) markers.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations in the present study are also consistent with this model, because the LCS appears to be a major source of both pallial-and subpallialderived cells of the amygdala. Furthermore, although LCS cells migrate to numerous other ventral telencephalic structures, in agreement with previous studies (Stoykova et al, 1996;Tole et al, 2005), we observe Pax6 ϩ and Dlx2 ϩ cells populating distinct subsets of developing amygdala nuclei such as the basolateral complex and basomedial and cortical nuclei. Furthermore, colocalization of both Pax6 ϩ and Dlx2 ϩ cells with the early neuronal marker TUJ1 indicates that at least some of these cells will differentiate into neurons.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…8). Previous studies indicated that COUP-TFII is also highly expressed in the amygdaloid nucleus, which some of the CGE cells are destined to populate (Lopes da Silva et al, 1995;Nery et al, 2002;Ló pez-Bendito et al, 2004;Tole et al, 2005). We also observed that some of the calretinin-positive cells in the hippocampus are COUP-TFII positive (data not shown).…”
Section: Characteristics Of Coup-tfii-positive Interneuronssupporting
confidence: 62%